Aboveground biomass and seasonal patterns of aboveground net primary productivity in five bamboo species in northern Laos. (23rd December 2019) - Xayalath, Singkone; Hirota, Isao; Tomita, Shinsuke; Nakagawa, Michiko
Abstract: Aims: Accurate estimates of bamboo biomass and net primary productivity (NPP) are required to evaluate the carbon sequestration potential of bamboo forests. However, relevant data that are important for climate change mitigation, have rarely been collected in regions outside of East Asia and India. Information on seasonal patterns of NPP and its components will enable the quantification of factors that influence the carbon balance in bamboo forests. In this study, we quantified the aboveground biomass (AGB) and aboveground NPP of five major bamboo species in northern Laos using monthly data collected over a 12-month period. Methods: All live culms in 10, 2 m × 2 m plots (for one monopodial bamboo species: Indosasa sinica ) and 30 clumps per species (for four sympodial bamboo species: Bambusa tulda, Cephalostachyum virgatum, Dendrocalamus membranaceus and Gigantochloa sp.) were numbered and measured at breast height. We set 10 or 20 litter traps per species to collect litterfall. Censuses of dead and recruited culms and litterfall collection were performed once per month for 12 months. Important Findings: The AGB was highest in I. sinica (59.87 Mg ha −1 ) and lowest in C . virgatum (11.54 Mg ha −1 ), and was mostly below the plausible global range for bamboos (32–256 Mg ha −1 ). The sympatric distribution of multiple bamboo species at the study sites may have suppressed the AGB in four of the five studied species. The aboveground NPP estimates were between 3.43 and 14.25 Mg ha −1 yr −1 ; those for D. membranaceus (8.20 Mg ha −1 yr −1 ) and I. sinica (14.25 Mg ha −1 yr −1 ) were comparable to mean global estimates for temperate evergreen forests (8.78 Mg ha −1 yr −1 ) and tropical moist forests (10.56 Mg ha −1 yr −1 ). High culm recruitment rates (15.20–23.39% yr −1 ) were major contributors to aboveground NPP estimates. Seasonal patterns of aboveground NPP were largely influenced by the phenology of the new culms. In the four sympodial bamboo species, new culms began to emerge following the onset of persistent rainfall, mainly in July and August. However, the sprouting of new culms in the monopodial species I. sinica followed a trend of increasing temperatures, mainly in March and April. Thus, our results indicate that bamboos have considerable potential for sequestering carbon in northern Laos, but that this potential may be affected by climate change.